Ex Vivo Costimulatory Blockade to Generate Regulatory T Cells From Patients Awaiting Kidney Transplantation. Issue 7 (11th March 2016) - Guinan, E. C.; Cole, G. A.; Wylie, W. H.; Kelner, R. H.; Janec, K. J.; Yuan, H.; Oppatt, J.; Brennan, L. L.; Turka, L. A.; Markmann, J.
Abstract : Short‐term outcomes of kidney transplantation have improved dramatically, but chronic rejection and regimen‐related toxicity continue to compromise overall patient outcomes. Development of regulatory T cells (Tregs) as a means to decrease alloresponsiveness and limit the need for pharmacologic immunosuppression is an active area of preclinical and clinical investigation. Nevertheless, the immunomodulatory effects of end‐stage renal disease on the efficacy of various strategies to generate and expand recipient Tregs for kidney transplantation are incompletely characterized. In this study, we show that Tregs can be successfully generated from either freshly isolated or previously cryopreserved uremic recipient (responder) and healthy donor (stimulator) peripheral blood mononuclear cells using the strategy of ex vivo costimulatory blockade with belatacept during mixed lymphocyte culture. Moreover, these Tregs maintain a CD3 + CD4 + CD25 + CD127 lo surface phenotype, high levels of intracellular FOXP3 and significant demethylation of the FOXP3 Treg‐specific demethylation region on allorestimulation with donor stimulator cells. These data support evaluation of this simple, brief Treg production strategy in clinical trials of mismatched kidney transplantation. Abstract : The authors demonstrate that the peripheral blood of uremic patients can generate donor antigen–specific T regulatory cells via an established in vitro costimulation blockade protocol, thereby setting the stage for use of these T regulatory cells as an immunotherapeutic treatment in renal transplantation.